THE EFFECTIVENESS OF VOCABULARY NOTEBOOK ON STUDENTS' VOCABULARY MASTERY - Desriani Nggolaon; Heriani Mombilia (English Education Study Program, 2021)
The purpose of this research was to determine whether the vocabulary notebook is effective in improving students’ vocabulary mastery. The method used to conduct this research is quasi experimental research. The population consist of 45 students of class VIII SMPN 2 Bulagi. Sampling was done by total sampling involving two classes, class A which is consist of 24 students as the experimental class and 1 students from class VIII B as the control class. In collecting data, researchers used test. After analyzing the data, the result showed that there was a significant difference between the results of increasing students’ vocabulary mastery using vocabulary notebook and those without vocabulary notebook. The score of pretest 58.6 in experimental class was increased significantly in the posttest 81.3. On the other hand, the pretest score in control class only increased from 56.0 to the posttest score 61.1. In addition, using 0.05 level of significant with 43 degree of freedom, it was found that the t-counted value 14.847 was greater than the t-table 2.016, so that Ha is accepted and H0 is rejected. It can concluded that the use of vocabulary notebooks is effective in increasing the students’ vocabulary at SMPN 2 Bulagi.